Association of Rictor with chromosomes during mitosis in MCF7 cells - Malanchuk, O.M. (Вiopolymers and Cell, 2015)
The mTOR kinase forms two multicomponent protein complexes (mTORC1 and mTORC2), where protein Rictor is a unique component of mTORC2. These two complexes differ both structurally and functionally and transmit signals to distinct downstream substrates. In contrast to mTORC1, comparatively little is known about functioning and regulation of mTORC2 and its components. Aim. To analyze of the particularity of Rictor subcellular localization in MCF7 cells. Methods. Immunofluorescence assay using confocal microscopy was applied. Results. Analysis of Rictor localization with anti N-terminal mAb revealed a different pattern of immunostaining in cells that was depended on cell cycle phase. For the first time it was shown that Rictor is at the exposed edge of condensed chromatin pool in MCF7 cells. Furthermore Z-stacking of cells revealed that character of association depends on mitosis phases. Conclusions. Our novel findings add to our understanding of functioning of both Rictor and mTORC2 in cell cycle progression. Кіназа mTOR формує два мультикомпонентних комплекси (mTORС1 та mTORС2, унікальним компонентом останнього є Rictor), які відрізняються як структурно, так і функціонально, та мають різні мішені. На відміну від mTORC1, відносно мало відомо про функціонування і регуляцію комплексу mTORC2 і його компонентів. Мета. Аналіз особливостей субклітинної локалізації Rictor в клітинах MCF7. Методи. Імунофлуорисцентний аналіз із використанням конфокальної мікроскопії було застосовано. Результати. Аналіз локалізації Rictor за допомогою моноклональних антитіл до N-термінального фрагменту Rictor продемонстрував диференційний патерн імунофарбування клітин в залежності від стадії клітинного циклу. Вперше виявлено значну поверхневу асоціацію Rictor з конденсованим хроматином в клітинах MCF7. Більш того, Z-стекінг клітин дав можливість зрозуміти характер асоціації, яка, як виявилось, залежить від фази мітозу. Висновки. Дані, отримані нами вперше, вносять вклад в розуміння функціонуваня як білкаRictor, так і комплекса mTORС2 в прогресії клітинного циклу. Киназа mTOR формирует два мультикомпонентных комплекса (mTORC1 и mTORC2, уникальным компонентом последнего является Rictor), которые отличаются как структурно, так и функционально и имеют разные мишени. В отличии от mTORC1, относительно мало известно о функционировании и регуляции комплекса mTORC2 и его компонентов. Цель. Анализ особенностей субклеточной локализации Rictor в клетках MCF7. Методы. Иммунофлюорисцентный анализ с использованием конфокальной микроскопии был применён. Результаты. Анализ локализации Rictor с помощью моноклональных антител к N-терминальному фрагменту Rictor выявил дифференциальный паттерн иммуноокрашивания клеток в зависимости от стадии клеточного цикла. Впервые удалось показать значительную поверхностную ассоциацию Rictor с конденсированным хроматином в клетках MCF7. Более того, Z-стекинг клеток позволил понять характер ассоциации, которая, как оказалось, зависит от фазы митоза. Выводы. Данные, полученные нами впервые, вносят вклад в понимание функционирования как белка Rictor, так и комплекса mTORС2 в прогрессии клеточного цикла.